Sosialisasi Pemanfaatan Limbah Air Cucian Beras Sebagai Pupuk Organik Cair (POC) di Desa Suak Air Hitam - Irwin Mirza Umami; Bramdo George Valentino Sinaga; Robin Syahputra; Stepanus Romo Kriswinardo Sinaga; Andreas Mai Ignatius Giawa; Faskah Yen Ribka Marpaung; Jauhariyah Putri Hanifah; Jenifer Octavia Usman; Laurencia Anggi Anggraeni; Nurjanah Nurjanah; Siti Astuti Sitompul (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The process of cooking rice generates a significant amount of waste in the form of rice wash water. In a household, it can produce at least 1 liter of rice wash water daily. Rice wash water contains nutrients necessary for plant growth, including N, P, K, phosphorus, iron, protein, fiber, amino acids, and zinc. The community service conducted by the students aimed to socialize and increase knowledge about the benefits of rice wash water as liquid organic fertilizer (LOF) to the community of Suak Air Hitam Village, Pekaitan District, Rokan Hilir Regency. This activity took place on August 14, 2024, at the Suak Air Hitam Village meeting hall. The methods used included theoretical presentations followed by guidance on making liquid organic fertilizer (LOF) using fermented rice wash water. The resulting LOF is used as liquid organic fertilizer in the Suak Air Hitam Village area and serves as a starter for further production carried out independently by the local community.